2002
DOI: 10.1177/153537020222700918
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in the Rat: Females are Protected Against the Pro-Oxidant Effect of a High Sucrose Diet

Abstract: Metabolic syndrome is more prevalent in men than in women. In an experimental dietary model of metabolic syndrome, the high-fructose–fed rat, oxidative stress has been observed in males. Given that estradiol has been documented to exert an antioxidant effect, we investigated whether female rats were better protected than males against the adverse effects of a high-sucrose diet, and we studied the influence of hormonal status in female rats. Males and females were first fed a sucrose-based or starch-based diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 41 publications
4
40
4
Order By: Relevance
“…However, there was no gender differences in our neonatal rats fed with cane syrup. This plausibly confirmed that the resistance to MetS by the female rats reported by these workers [28] is associated with age and the hormonal factor responsible manifest at adult age of the rodent's life [29]. 3.96±0.20 3.74±0.34 * value highly significant (p < 0.0001) across the column; No significant difference (p ≥ 0.05) in the other circulating metabolic substrates amongst the control and treatment groups after 10-day treatment.…”
Section: Metabolic Substratessupporting
confidence: 90%
See 1 more Smart Citation
“…However, there was no gender differences in our neonatal rats fed with cane syrup. This plausibly confirmed that the resistance to MetS by the female rats reported by these workers [28] is associated with age and the hormonal factor responsible manifest at adult age of the rodent's life [29]. 3.96±0.20 3.74±0.34 * value highly significant (p < 0.0001) across the column; No significant difference (p ≥ 0.05) in the other circulating metabolic substrates amongst the control and treatment groups after 10-day treatment.…”
Section: Metabolic Substratessupporting
confidence: 90%
“…Male rats are not known to be resistant to abdominal obesity, hyperglycaemia, dyslipidaemia and other risk factors of renal and metabolic diseases. As documented by some researchers [7], adult female rodents are less susceptible to the adverse effects of sucrose consumption [28]. However, there was no gender differences in our neonatal rats fed with cane syrup.…”
Section: Metabolic Substratessupporting
confidence: 62%
“…Increases in the fructose load to the liver, through diets enriched with sucrose or fructose or via portal vein fructose infusion, can alter the bnormalQ postprandial intrahepatic milieu [12,[59][60][61][62][63][64]. We propose that these changes serve as signals of nutrient excess and elicit rapid responses that ultimately influence hepatic gene expression and insulin action.…”
Section: Hepatic Sensitivity To Nutrients and Unique Properties Of Frmentioning
confidence: 99%
“…Alternatively, female rats appear to have a protection against diet-induced pathological alterations, such as hypertension and oxidative stress (Roberts et al, 2001;Busserolles et al, 2002).…”
Section: Introductionmentioning
confidence: 99%